The Relationship between Interest Rate, Exchange Rate, Inflation Rate and GDP to Foreign Direct Investment Inflows in Malaysia - Mohd Sufli, Yusof (2009)
Malaysia received substantial amounts of foreign direct investment (FDI) inflows over the past decades. This study examines the relationship between interest rate, exchange rate, inflation rate and gross domestic production (GDP) to FDI inflows in Malaysia. The study uses quarterly data from 2000 to 2007 and control for determinants of their inwards FDI in Malaysia. The purpose of the study is also to find out the most important variables in determining FDI inflows to Malaysia. Finally, the results which were obtained by using normal time series regressions show that the most important determinant are GDP and followed by interest rate. Both independent variables also show the positive sign of relationship with FDI inflows in Malaysia. However, the inflation level is not a significant variable.